Cost-effectiveness of precision medicine in the fourth-line treatment of metastatic lung adenocarcinoma: An early decision analytic model of multiplex targeted sequencing. (May 2017) - Doble, Brett; John, Thomas; Thomas, David; Fellowes, Andrew; Fox, Stephen; Lorgelly, Paula
Highlights: The use of MTS panels is associated with additional costs and uncertainty as to their impact on overall outcomes. ICERs for MTS were very unfavourable, but a number of parameters were identified to have large impacts on model results. Altering mortality rates and the number of hospitalizations for true positive patients had the largest impacts on the ICERs. Other parameters related to testing and the cost of off-label targeted therapy had relatively small impacts on the ICERs. Scenario analyses showed that advances in technology and/or scientific understanding will have limited impact on the cost effectiveness of MTS. Abstract: Objectives: To identify parameters that drive the cost-effectiveness of precision medicine by comparing the use of multiplex targeted sequencing (MTS) to select targeted therapy based on tumour genomic profiles to either no further testing with chemotherapy or no further testing with best supportive care in the fourth-line treatment of metastatic lung adenocarcinoma. Methods: A combined decision tree and Markov model to compare costs, life-years, and quality-adjusted life-years over a ten-year time horizon from an Australian healthcare payer perspective. Data sources included the published literature and a population-based molecular cohort study (Cancer 2015). Uncertainty was assessed using deterministic sensitivity analyses and quantified by estimating expected value of perfect/partial perfect information. Uncertainty due to technological/scientific advancement was assessed through a number of plausible future scenario analyses. Results: Point estimate incremental cost-effective ratios indicate that MTS is not cost-effective for selecting fourth-line treatment of metastatic lung adenocarcinoma. Lower mortality rates during testing and for true positive patients, lower health state utility values for progressive disease, and targeted therapy resulting in reductions in inpatient visits, however, all resulted in more favourable cost-effectiveness estimates for MTS. The expected value to decision makers of removing all current decision uncertainty was estimated to be between AUD 5, 962, 843 and AUD 13, 196, 451, indicating that additional research to reduce uncertainty may be a worthwhile investment. Plausible future scenarios analyses revealed limited improvements in cost-effectiveness under scenarios of improved test performance, decreased costs of testing/interpretation, and no biopsy costs/adverse events. Reductions in off-label targeted therapy costs, when considered together with the other scenarios did, however, indicate more favourable cost-effectiveness of MTS. Conclusion: As more clinical evidence is generated for MTS, the model developed should be revisited and cost-effectiveness re-estimated under different testing scenarios to further understand the value of precision medicine and its potential impact on the overall health budget.